Comprehensive Review of Healthcare Systems and Their Evolving Structures - Alqarafi, Ohood Mustafa; Abusaaq, Abdulrhman Mana; Alameer, Mustafa Hussien; Al-Zaher, Zahrah Jassem; AlSafwani, Safa Salman; saihati, Fatimah Hussain Ali; Alqahtani, Ghazeel Mubarak; Alanazi, Fatimah Faraj Hijj; hamyan , Aziza hussain ali al; Al Khaiwani, Yousef Nasser Hassan (Journal of Ecohumanism, 2024)
Physical assessment of healthcare organizations shows they are experiencing changes in response to the dynamic global healthcare needs, technologies, and political, economic, and social systems. This extensive literature review explores the various dimensions of the HC system, including governance and financing, the health workforce, and models of the service delivery systems. It seeks to look at the various issues confronting healthcare delivery systems across the developed and developing worlds with special reference to policies, technology, and human resources. The current paper offers insight into how healthcare systems are evolving to enhance healthcare access, quality, and efficiency from the case studies and additional literature. The review also outlines some emerging trends, such as value-based care, personalized medicine, and digital tools in health. The implications of the knowledge support the effectiveness of the overall system transformation to establish firm and fair healthcare for the actual people's needs.